Rheostatic Balance of Circadian Rhythm and Autophagy in Metabolism and Disease - Wang, Xiang; Xu, Zhijie; Cai, Yuan; Zeng, Shuangshuang; Peng, Bi; Ren, Xinxin; Yan, Yuanliang; Gong, Zhicheng (Frontiers in Cell and Developmental Biology, 2020)
Circadian rhythms are physical, behavioral and environmental cycles that respond primarily to light and dark, with a period of time of approximately 24 h. The most essential physiological functions of mammals are manifested in circadian rhythm patterns, including the sleep-wake cycle and nutrient and energy metabolism. Autophagy is a conserved biological process contributing to nutrient and cellular homeostasis. The factors affecting autophagy are numerous, such as diet, drugs, and aging. Recent studies have indicated that autophagy is activated rhythmically in a clock-dependent manner whether the organism is healthy or has certain diseases. In addition, autophagy can affect circadian rhythm by degrading circadian proteins. This review discusses the interaction and mechanisms between autophagy and circadian rhythm. Moreover, we introduce the molecules influencing both autophagy and circadian rhythm. We then discuss the drugs affecting the circadian rhythm of autophagy. Finally, we present the role of rhythmic autophagy in nutrient and energy metabolism and its significance in physiology and metabolic disease.